2019
DOI: 10.1108/ijge-05-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Context, gender and entrepreneurial intentions

Abstract: Purpose This paper aims to explore how gender differences in entrepreneurial intentions (EI) change when entrepreneurship education (EE) is added to the force field of macro-social stimulants and inhibitors of female EI in the particular context of the United Arab Emirates (UAE). Design/methodology/approach The study is based on a pre-post survey with entrepreneurship students and students with a similar profile enrolled in other courses (N = 246) at three universities. The three main hypotheses are evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 58 publications
1
34
1
3
Order By: Relevance
“…Therefore, studying gender differences in entrepreneurial intentions and behavior could help researchers and policymakers to foresee reasons for that kind of lower entrepreneurship activities [67]. There may be discrepancies in different types of academic programs, whether business or not [68][69][70]. However, most of the research about entrepreneurial intention and entrepreneurship presents a bias because it is based on cases in developed western countries, such as the US and the UK [71].…”
Section: Gendermentioning
confidence: 99%
“…Therefore, studying gender differences in entrepreneurial intentions and behavior could help researchers and policymakers to foresee reasons for that kind of lower entrepreneurship activities [67]. There may be discrepancies in different types of academic programs, whether business or not [68][69][70]. However, most of the research about entrepreneurial intention and entrepreneurship presents a bias because it is based on cases in developed western countries, such as the US and the UK [71].…”
Section: Gendermentioning
confidence: 99%
“…9770/jesi.2021.8.4(24) The institutional framework generally affects entrepreneurship by influencing the uncertainty and expected return on investment regardless of the gender (Chowdhury, Audretsch 2014). The informal institutions of norms, values, culture, and stereotypes are often listed as causes for the gender gap in entrepreneurship (Petrović, Radukić 2019;van Ewijk, Belghiti-Mahut 2019). The prototypical entrepreneur is perceived as masculine and individual; these features are male-stereotypes (Orser et al 2011;Gimenez-Jimenez et al 2020), while females are stereotypically perceived as caring and nurturing (Orser et al 2011).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Muller and Thomas (2001) suggested that there is an increasing need for universitytrained entrepreneurs due to the dynamic technology and global competition growth as the business success will be dependent upon founder's education and training. Students are widely used as a sample in researching traits, especially their influence on entrepreneurial intention in different contexts (Muller & Thomas, 2001;Gürol & Atsan, 2006;Altinay et al, 2012;Farrukh et al, 2018;Van Ewijk & Belghiti-Mahut, 2019). Sampling students also provides control over the testing environment due to their accessibility and convenience.…”
Section: Respondents and Data Collection Proceduresmentioning
confidence: 99%